Effect of Trichoderma spp., Paecilomyces lilacinus and nematicide injection into the pseudostem, on Radopholus similis control and banana production - Vargas, Randall (2015)
The effect of Trichoderma spp., strains PB17 and B23, Paecilomyces lilacinus UNA strain, and nematicide injecting into the pseudostem, on nematode control and banana (Musa AAA) production was evaluated. A commercial banana farm infested with nematodes and planted with the cultivar Grande Naine was selected. A randomized complete block design with 6 replications was used. Monthly applications at 1 * 109 cfu.ml-1 of each strain were made during 20 months. Chemical nematicide application on the soil surface was made every 4 months and injection of oxamyl into the pseudostem was performed every 3 months. Root samples were taken every month in each replicate, for nematode analysis. It was not possible to reduce nematode populations on plants treated with P. lilacinus UNA strain nor with Trichoderma spp. PB17 and B23 strains. However, plants treated with these strains showed higher bunch weight (p=0.0375) and girth (p=0.0402) of the mother plant, when compared with plants without such application. The plants injected with oxamyl and those treated with the rotation of nematicides on the soil surface showed a higher percentage of functional roots (p<0.0241) and reduced (p<0.0001) the total number of nematodes in 43 and 41% respectively, when compared with the untreated control. The plants injected with oxamyl increased bunch weight by 3.2 kg (p=0.0006) and showed greater (p<0.0478) number of hands, calibration, length of the fruit and stem circumference, as compared to plants without application. There were no differences in production variables evaluated when comparing the rotation of nematicides on the soil surface with injecting oxamyl on the pseudostem.